India's Pattern of Development What Happened, What Follows? - Subramanian, Arvind (International Monetary Fund, 2006)
India has followed an idiosyncratic pattern of development, certainly compared with other fast-growing Asian economies. While the importance of services rather than manufacturing is widely noted, within manufacturing India has emphasized skill-intensive rather than laborintensive manufacturing, and industries with higher-than-average scale. Some of these distinctive patterns existed prior to the beginning of economic reforms in the 1980s, and stem from the idiosyncratic policies adopted after India''s independence. Using the growth of fastmoving Indian states as a guide, we conclude that India may not revert to the pattern followed by other countries, despite reforms that have removed some policy impediments that contributed to India''s distinctive path